Performance prediction of trailing-edge cooling system of gas turbine blade using detached eddy simulation - Jamaldi, Agus; Hassan, Hassan Khamis (Department of Mechanical Engineering Universitas Muhammadiyah Surakarta, 2020)
This study aims to evaluate the performance of the trailing-edge (TE) cooling system in a gas turbine blade. Eddy Simulation (DES), based on the turbulence model of Spallart-Almaras (SA), was used to simulate the TE cooling system. A TE configuration with a five-row staggered pin-fin arrangement was employed as a computational domain. Three parameters, i.e., the coefficient of heat transfer on the pin-fins surface (hpin), the coefficient of discharge (CD), and the effectiveness of adiabatic film cooling were used to assess the performances. The findings denoted that the heat transfer fluctuations occurred on the surface of the pin-fins in each row. The discharge coefficient increased with the rising of the blowing ratio. The trend predicted data ofÂ effectiveness were in good agreement with realistic discrepancies compared to other researches, mainly for higher blowing ratio. The average effectiveness along the cut-off region was to be sensitive to the changes of the blowing ratio, which was attributed to the structures of turbulent flow along the mixing region.